Impact of the COVID-19 pandemic on gastrointestinal endoscopy in Africa - Ebigbo, Alanna; Karstensen, John Gásdal; Bhat, Purnima; Ijoma, Uchenna; Osuagwu, Chukwuemeka; Desalegn, Hailemichael; Oyeleke, Ganiyat K.; Gebru, Rezene B.; Guy, Claire; Antonelli, Giulio; Vilmann, Peter; Aabakken, Lars; Hassan, Cesare (Endoscopy International Open, 2020)
Background and study aims As with all other fields of medical practice, gastrointestinal endoscopy has been impacted by the COVID-19 pandemic. However, data on the impact of the pandemic in Africa, especially sub-Saharan Africa are lacking.Methods A web-based survey was conducted by the International Working Group of the European Society for Gastrointestinal Endoscopy and the World Endoscopy Organization to determine the impact and effects the COVID-19 pandemic has had on endoscopists in African countries.Results Thirty-one gastroenterologists from 14 countries in north, central, and sub-Saharan Africa responded to the survey. The majority of respondents reduced their endoscopy volume considerably. Personal protective equipment including FFP-2 masks were available in almost all participating centers. Pre-endoscopy screening was performed as well.Conclusion The COVID-19 pandemic has had a substantial impact on gastrointestinal endoscopy in most African countries; however, the impact may not have been as devastating as expected.